Students' Direct and Deferred Concept Understanding and Self-Efficacy Using the Inverted Learning Approach in Biology - Rolly James, Cheng (SEAMEO QITEP in Science, 2024)
The increasing availability of data and technological advancements, along with the influx of various educational platforms, reflects the evolving knowledge acquisition and transfer paradigm in the digital age. This highlights the need for educators and institutions to adapt their approaches and recognise the significance of harnessing educational technology as a powerful tool to promote the widespread adoption of flexible online learning. An Inverted Learning Approach (ILA) is an innovative pedagogical design that maximises off-class learning by providing students with access to instructional resources. This allows students to self-pace their learning and become more independent and ready for in-class activities. The study followed a quasi-experimental study, employing a two-group pre-test and post-test controlled group design. It zeroed in on determining how ILA affects the direct and deferred concept understanding and self-efficacy of Science, Technology, Engineering, and Mathematics (STEM) students enrolled in a biology course. The use of ILA was the treatment given to the experimental or intervention group, while the Expository Online Teaching (EOT) was given to the comparison group. A total of 287 STEM students were involved in the study and taught by the same teacher to maintain parity of conditions except for the treatment. Informed consent and assent forms were likewise collected as required by the Research Ethics Board to safeguard the research participants, monitor likely risks and benefits, and establish high ethical standards where the study was conducted. Gagne’s nine instructional events were designed in the learning plan to develop a clear instruction flow between the two groups. The students' levels of direct and deferred concept understanding were measured using the Researcher-validated Biology Achievement Test (RBAT) on the pre-test, post-test, and postponed test, and the results were analysed using ANOVA and post-hoc tests. Results revealed that students taught using ILA had significantly higher mean gains in post-test and retention test scores than those taught using the EOT. The level of self-efficacy among ILA students has also shown a significant increment compared to their counterparts. In other words, ILA significantly improved students' direct and deferred concept understanding and self-efficacy.